Strategi Public Relations Astra International dalam Mempertahankan Reputasi di Era Kenormalan Baru - Amelia Anggraeni Sulistiyo; Chininta Rizka Angelia (Jurnal Komunikasi Profesional, 2023)
Public Relations generally exists in every large company and becomes the "face" or representation of the company. Management also reports about the company, communication through PR. The arrival of the COVID-19 virus has had a significant impact on various sectors of life in Indonesia. Overcoming the pandemic requires a synergy between the government and other parties that can reduce the impact felt by the Indonesian people. Seeing this situation, companies from various business sectors show concern in their own ways, such as carrying out an activity and establishing relevant programs. When a company wants to deliver concrete actions to help its public, Public Relations as a representative of the company comes down to get involved so that the delivery of messages from the company to the public can be right on target. One of the largest companies in Indonesia, Astra International, through its Public Relations division, has established a PR program for the #SemangatSalingBantu movement to help others in need. The purpose of this research is to find out the strategy used by Public Relations in maintaining the reputation of PT Astra International Tbk in the new normal era through the #SemangatSalingBantu movement. This research uses case study research method, descriptive qualitative approach, and data collection by interviewing two participants and one expert informant as well as documentation study. The results were analyzed using Ronald D. Smith's concept of PR strategy (2017) and analysis using the pattern matching technique. The dominant concept used is the concept of Smith's PR strategy, as well as the concept of the Nowak and Warneryd campaign models. The results showed that the PR strategy of the #SemangatSalingBantu movement used a proactive communication strategy; being relevant in every aspect of communication and focusing on digital communication. Using owned media as an effective communication tactic Keywords: Public Relations Strategy; Astra International; #SemangatSalingBantu Movement; New Normal Era; Reputation